2022
DOI: 10.3389/fnut.2022.839145
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation With Pleurotus Ostreatus Enhances the Prebiotic Properties of Germinated Riceberry Rice

Abstract: Rice is the staple food for more than half of the world's population. In recent years, awareness of the health benefits of colored rice varieties and germinated rice has gradually increased. Riceberry rice (R), a black-purple variety, was germinated and subsequently fermented with Pleurotus ostreatus mycelium (M) to improve nutrient quality and prebiotic properties. The γ-aminobutyric acid (GABA) and β-glucan contents were measured daily for a total of 4 days. The prebiotic activities of R, germinated Riceberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Based on these experimental results, the germinated Sang Yod brown rice expressed prebiotic properties. This finding was consistent with the previous study [19]. The results obtained in this study showed that the probiotics could grow using the prebiotic as a carbon source.…”
Section: Prebiotic Property Of Germinated Sang Yod Brown Rice Powdersupporting
confidence: 94%
“…Based on these experimental results, the germinated Sang Yod brown rice expressed prebiotic properties. This finding was consistent with the previous study [19]. The results obtained in this study showed that the probiotics could grow using the prebiotic as a carbon source.…”
Section: Prebiotic Property Of Germinated Sang Yod Brown Rice Powdersupporting
confidence: 94%
“…Recently, the prebiotic activity of P. ostreatus has become an important tool in the food industry due to its important role to improve and balance the composition of microbiota in the gut, which is linked to the health conditions of the host [67]. Many studies have also been published on the enhancing P. ostreatus prebiotic properties for many foods or crops such as olive byproducts [68], riceberry rice [67], and processed cheese [69]. There are many common carbohydrates that are well-known as prebiotics (i.e., inulin, lactulose, fructo-oligosaccharides, galacto-oligosaccharides, and β-glucan) in the human diet [67,70].…”
Section: Medicinal and Pharmacological Attributes Of P Ostreatusmentioning
confidence: 99%
“…The experiment including the germinated Riceberry rice (GR) was performed by following the previous method described by Soodpakdee et al [15]. In brief, Riceberry rice (RR) was rinsed with sterile distilled water and soaked in plastic containers covered with colanders at 25 C for 12 h. Three cycles of these actions were performed before discontinuing the germination process at 36 h. The germinated Riceberry rice (GR) was dried in a hot air oven (Memmert/une-500), which was set at 60 C temperature for 24 h to stop the enzyme activity responsible for germination.…”
Section: Sample Preparation and Germination Methodsmentioning
confidence: 99%
“…The protocol for GABA content analysis was done according to the procedure described by Soodpakdee et al (2022) [15]. The range of GABA standard (Sigma-Aldrich) was provided at 0 to 100 ppm to create a standard curve.…”
Section: Extraction and Determination Of Gaba Content In Riceberry Ri...mentioning
confidence: 99%
See 1 more Smart Citation